VegAndes: the vegetation database for the Latin American highlands - Peyre, Gwendolyn (2022)
In the era of Big Data, Latin American countries and biomes remain underrepresented. To remediate this issue, promoting repositories for biodiversity data focused on Latin America is a main priority. VegAndes -Dpt the vegetation database for the Latin American highlands (GIVD: SA-00-005), is a novel dataset for georeferenced and standardized information on vascular pants in the region. The database compiles 5,340 vegetation plots sampled above the montane treeline and below the permanent snowline in 11 Latin American countries and spanning over seven decades. VegAndes currently encompasses 5,804 taxon names, corresponding to 3,858 accepted names, as well as 136 syntaxon names. The database is nested within a scientific consortium of Latin American experts on highland vegetation and piloted from the University of the Andes (Colombia). Because the VegAndes data can support multi-scale studies in botany, ecology and biogeography, the database makes an essential contribution to biodiversity research and management perspectives in Latin America.